Disiplin dan nilai-nilai religius dalam membentuk perilaku tagguh dan tanggung jawab - Yudo Handoko, Yudo Handoko (Indonesian Journal of Islamic Religious Education, 2023)
This research explores the roles of discipline and religious values in shaping the resilience and responsibility of students at SMP Nidaul Quran in Kabupaten Sarolangun. Employing a qualitative approach and a case study design, data were gathered through interviews, observations, and document analysis. The findings indicate that discipline plays a crucial role in molding students' character, emphasizing an educational approach focused on character development. SMP Nidaul Quran successfully aligns discipline with religious values, cultivating students who are resilient and responsible. The role of teachers as moral guides and the active support of parents are also crucial factors. This research contributes to the development of knowledge and practices in Islamic education. The integration of religious values not only produces academically competent students but also in stills strong moral integrity. The holistic approach involving teachers, parents, and religious values serves as a model for other Islamic educational institutions. These practices promote the understanding that Islamic education shapes the hearts and souls of students to be resilient, responsible, and prepared to face life's challenges.